Mass Cultivation of Entomopathogenic Nematode in Artificial Media - Indriyanti, Dyah Rini; Muharromah, Nur Lailatul (Biosaintifika: Journal of Biology & Biology Education, 2016)
Entomopathogenic nematodes Entomopathogenic nematodes (EPN) of the genera Heterorhabditis and Steinernema are commercially used to control pest insect. EPN is widely cultivated through in-vivo and in vitro methods. This research aims to discover the abundance of EPN cultivated in various artificial media. Seven types of media composition were tested in this research: media A (yeast + soybean powder), media B (yeast + chicken liver), media C (yeast + dog food), media D (yolk + soybean powder), media E (yolk + chicken liver), media F (yolk + dog food), and media G (yeast + yolk + dog food). Each media was inoculated in 1.2x103JI/mL. The growth of EPN was observed weekly in 4 weeks. Results showed that EPN could be cultivated using various media; media D, E, F, and G. Highest abundance of EPN is found in the second week of media D for 28164 JI/ml.Cell harvesting is suggested to be conducted during the first and second week to obtain maximum abundance of EPN.How to CiteIndriyanti, D., & Muharromah, N. (2016). Mass Cultivation of Entomopathogenic Nematode In Artificial Media. Biosaintifika: Journal of Biology & Biology Education, 8(1), 111-118.